Educative Communication Style of @dailyhaid in Women’s Fiqh Literacy Among Generation Z - Nabilatus Sholihah; Muhammad As’ad (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
The increasing use of social media has transformed Islamic communication, particularly in delivering women’s fiqh education to Generation Z. This study aims to analyze the educative communication style employed by the Instagram account @dailyhaid in promoting women’s fiqh literacy among Generation Z. Using a qualitative case study with a digital ethnography approach, data were collected through virtual observations of Instagram content, audience interactions, and in-depth interviews with the account founder and eight Generation Z followers. The findings reveal that @dailyhaid applies an educative communication style characterized by empathetic, assertive, and non-judgmental communication. Religious messages are presented through simple language, visual infographics, and interactive features that encourage audience participation and create a psychologically safe learning environment. These communication practices improve followers’ understanding of women’s fiqh, increase emotional comfort when discussing sensitive religious issues, and strengthen confidence in applying Islamic teachings in everyday life. This study contributes to Islamic communication studies by proposing empathetic assertive digital da’wah as a communication model for discussing sensitive women’s fiqh issues through digital media, highlighting the importance of combining clear religious guidance with empathy and participatory communication to enhance religious literacy among Generation Z.